Consuming Representations of Korean TV Dramas among Indonesian Muslim Youth - Rosidi, Imron (Universitas Semarang, 2020)
This article dealt with Korean TV dramas consumption among Muslim youth in Pekanbaru. It aimed to undestand their interpretations on the television dramas. The values of being a Muslim was constantly under scrutiny by the image representation in Korean TV Dramas. As transnational cultural products, they were considered as reducing Islamic values for Muslim youth. Using ethnographic study, forty two informants were selected based on a purposive sampling technique in which they loved on consuming Korean TV dramas. This article found that Muslim youth were active audiences consuming and interpreting Korean TV dramas. This can be seen from two characteristics. The first is that Muslim youth consumption of Korean TV dramas was not dominantly done through television medium, but through their lapptop. As a result, their position as an active audiences or viewers was obvious. This was because the dramas to be watched were not interrupted by some advertisements. The audiences could also actively watch them without depending on the schedule decided by television stations. The second is that young Muslims watching Korean TV dramas did not accept some representations contradictory with their Islamic identity. However, some of Korean TV dramas were accepted due to their proximity with Islamic values.